(untitled) (Bioscience Journal, 2017)
The physalis production has caused interest of producers, consumers and traders due to its easy growing, high nutritional value and economic value added. The objective of this study was to evaluate the growth and characterize the symptoms of macro and micronutrient deficiencies in physalis seedlings (Physalis peruviana L.). The seedlings were grown in complete nutrient solution and also in solutions with individual omissions of N, P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn, using the missing element technique. Visual symptoms of nutrient deficiency and the dry matter production of shoot and root, respectively taken at 68 and 150 days after treatment application were evaluated. Omissions of macro and micronutrients caused visual symptoms of nutrient deficiencies common to other species. Nutrient deficiencies limited the total dry matter production in the following order: N > S> P> K > Ca > Mg for macronutrients and Fe > B > Zn > Mn > Cu for micronutrients, respectively.